Asymmetric coupling of Au nanospheres on TiO2 nanochannel membranes for NIR-gated artificial ionic nanochannels. Issue 97 (20th November 2019) - Yang, Lingling; Qu, Kuanzhi; Guo, Junli; Xu, Huijie; Dai, Zhenqing; Gao, Zhi-Da; Song, Yan-Yan
Abstract : Au nanospheres are selectively formed at one tip of TiO2 nanochannels by combining a photocatalytic reaction with limited penetration of light. The closed–open switching behavior of the temperature-responsive polymer is achieved under NIR irradiation. Abstract : Au nanoparticles were asymmetrically fabricated at one tip of TiO2 nanochannels by combining a photocatalytic reaction and limited penetration of light. Using the asymmetrical nanochannel-based membrane as a plasma absorber, near-infrared-gated artificial ionic nanochannels were designed.